Str Locus Mutations In Paternity Case - Racy Youngest; Vira Saamia; Dwi Ana Oktaviani; Setia Betaria Aritonang; I Made Wiranatha; Irfan Rofiq (Universitas Airlangga, 2022)
DNA analysis is widely applied in solving forensic cases, especially Short Tandem Repat (STR) because of its advantages. In identifying the individual, the National Police compared the individual's DNA with that of his parents. Each anal has a pair of DNA fragments of which half are inherited by the father and the remainder by the mother according to Mendel's Law of Segregation. In this study, we compared DNA typing between the child and the mother with the help of PCR extracted by the Chelex method to find the mother fragment and obtain the father fragment. A child is the biological child of the alleged father if he or she has less than 2 exclusion STR loci. The results of this study revealed that all paternal fragments from the child were identical to the DNA fragments of the alleged father, except for one locus, namely CSF1PO which had a mutation. Mutations in the STR locus lower the paternity index, although it can still be concluded that the child is the biological child of the alleged father. Keywords: Paternity Test, DNA, STR, Mutation